Wild manihot species do not possess C4 photosynthesis - Calatayud, Paul-André; Baron, C.H.; Velásquez, H.; Arroyave, José A.; Lamaze, T (Oxford University Press, 2002)
Cultivated cassava (Manihot esculenta) has a higher rate of photosynthesis than is usual for C3 plants and photosynthesis is not light saturated. For these reasons it has been suggested that cultivated cassava could be derived from wild species possessing C4 photosynthesis. The natural abundance of 13C and activities of phosphoenolpyruvate carboxylase and phosphoglycolate phosphatase were measured in leaves of 20 wild cassava species to test this hypothesis. All the species studied, including M. flabellifolia the potential wild progenitor of cultivated cassava, clearly exhibited C3 not C4 characteristics.